Impromptu [videorecording (DVD)] - Davis, Judy, 1956-; Grant, Hugh; Patinkin, Mandy; Peters, Bernadette; Thompson, Emma (Olive Films, 2015)
Brazenly forward George Sand and frail, romantic Frederic Chopin are drawn together as lovers by an unnerving bond that cannot be broken despite the best efforts of those around them to keep them apart.